Plan de Internacionalización para la empresa ‘Taller de cerámicas pflorez’ del municipio de Ráquira, Boyacá (2020)
This research explores the current situation of the company Taller de Cerámicas PFLOREZ, producer and marketer of artisan earthenware made from clay, identifying its strengths, weaknesses, opportunities and threats using a DOFA matrix. Once the diagnosis was made, a market investigation was carried out where it was found that the country with the greatest potential for the export of clay Mug wells is Mexico, more specifically Guadalajara, on the other hand, the costs of DFI were identified, as well as the procedures and documents necessary for the entry of the product to the Mexican market. Lastly, internationalization strategies were established and it was concluded that exporting under INCOTERM DDP is not feasible due to the high logistics costs which the PFLOREZ company is not capable of assuming at the moment, however it is found that the price of The sale of the product in Mexico is very competitive, so it is recommended that the company carry out small exports through 472, as well as look for business opportunities to carry out exports under an INCOTERM EXW or FCA.